Perancangan Sistem Informasi Aplikasi Promosi Pegawai di Lingkungan Kementerian Agama Kota Medan - Wini Istya Sari Lubis Wini; Helmi Fauzi Siregar; Muhammas Yasin Simargolang (Ali Institute of Reseach and Publication, 2024)
A promotion is an application for a promotion given to civil servants who have reached a certain work period limit for promotion to rank or position, namely once every two years and if they have fulfilled the requirements based on the applicable laws and regulations. At the Medan City Ministry of Religion Office, promotions are carried out every two years within two months and are still done manually, namely when submitting promotion documents, the personnel department checks the civil servant decree and notifies the employee concerned if there are incomplete requirements that must be completed to be submitted to Promotion if there are problems requires a long time to check employee data and employee files which must be completed as a condition for applying for promotion, considering that there is a risk of losing employee files. Applications for promotions that are made manually also often experience delays in issuing promotion letters. The result of this research is an information system in the form of a website for applying for employee promotions which was built to assist the Medan City Ministry of Religion Office, especially the personnel department, in scheduling and issuing promotion decisions and can assist in filling out employee decision letters quickly, accurately and personally.